Continuous exposure of nicotine and cotinine retards human primary pterygium cell proliferation and migration. Issue 3 (27th September 2018) - Yang, Qichen; Jhanji, Vishal; Tan, Sze Qin; Chan, Kwok Ping; Cao, Di; Chu, Wai Kit; Zhang, Mingzhi; Pang, Chi Pui; Ng, Tsz Kin
Abstract: Pterygium is a triangular‐shaped hyperplastic growth, characterized by conjunctivalization, inflammation, and connective tissue remodeling. Our previous meta‐analysis found that cigarette smoking is associated with a reduced risk of pterygium. Yet, the biological effect of cigarette smoke components on pterygium has not been studied. Here we reported the proliferation and migration properties of human primary pterygium cells with continuous exposure to nicotine and cotinine. Human primary pterygium cells predominantly expressed the α5, β1, and γ subunits of the nicotinic acetylcholine receptor. Continuous exposure to the mixture of 0.15 μM nicotine and 2 μM cotinine retarded pterygium cell proliferation by 16.04% ( P  = 0.009) and hindered their migration by 11.93% ( P  = 0.039), without affecting cell apoptosis. SNAIL and α‐smooth muscle actin protein expression was significantly downregulated in pterygium cells treated with 0.15 μM nicotine‐2 μM cotinine mixture by 1.33‐ ( P  = 0.036) and 1.31‐fold ( P  = 0.001), respectively. Besides, the 0.15 μM nicotine‐2 μM cotinine mixture also reduced matrix metalloproteinase (MMP)‐1 and MMP‐9 expressions in pterygium cells by 1.56‐ ( P  = 0.043) and 1.27‐fold ( P  = 0.012), respectively. In summary, this study revealed that continuous exposure of nicotine and cotinine inhibited human primary pterygium cell proliferation and migration in vitro by reducing epithelial‐to‐mesenchymal transition and MMP protein expression, partially explaining the lower incidence of pterygium in cigarette smokers. Abstract : Continuous exposure of nicotine and cotinine retards human primary pterygium cell proliferation and migration with reduction in epithelial‐to‐mesenchymal transition (EMT) marker and matrix metalloproteinase (MMP) expressions. There could be an inverse relationship between cigarette smoking and pterygium incidence.